An Integrated Brain–Hand Worksheet Design to Foster Cognitive and Fine Motor Development in Early Childhood - Ramli, Syamsul Alam; Eka Poppi Hutami; Jacinto de Oliveira Junior; Lisda (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study addresses the limitations of conventional early childhood worksheets, which often separate cognitive and fine motor activities into isolated tasks. The study aims to develop and evaluate a Brain–Hand integrated worksheet design that combines cognitive processing and fine motor engagement within a single learning activity.Design/methods/approach – An explanatory sequential mixed-methods design with a one-group pretest–posttest approach was employed. Quantitative data were collected through structured observations and teacher questionnaires, while qualitative data were obtained through semi-structured interviews with selected teachers. Sixty early childhood educators participated as implementers and evaluators, with developmental observations conducted among 312 children aged 3–6 years. Quantitative data were analyzed using descriptive statistics and paired-sample t-tests, whereas qualitative data were analyzed thematically.Findings – The results showed significant improvements in children’s motor and cognitive development following the implementation of Brain–Hand worksheets. Paired-sample t-test results indicated a significant increase in motor skill scores (t(311) = 4.56, p < .001, Cohen’s d = 0.80) and cognitive skill scores (t(311) = 4.12, p < .001, Cohen’s d = 0.75). Teachers also reported high levels of student engagement and positive perceptions regarding the integration of cognitive and fine motor activities. These findings indicate that a structured worksheet design integrating cognitive and fine motor tasks is associated with improvements across both developmental domains.Research implications/limitations – The findings should be interpreted considering several limitations, including purposive sampling, the absence of a control group, and the relatively short intervention period. These factors limit the generalizability of the findings and highlight the need for future longitudinal studies using more objective developmental assessment approaches.Practical implications – The Brain–Hand worksheet model provides educators with a structured approach for designing multisensory learning activities that simultaneously engage children’s thinking processes and fine motor coordination in early childhood classrooms.Originality/value – Unlike conventional worksheets that emphasize cognitive or motor activities separately, the Brain–Hand design systematically integrates both domains within a single instructional framework. This study contributes an applied model for implementing embodied cognition principles in early childhood classroom practices and provides empirical evidence regarding cognitive–motor integration through structured worksheet design.Paper type Research paper